Encontros e desencontros das Três Marias de Rachel de Queiroz - uma leitura em O Quinze, Dôra, Doralina e Memorial de Maria Moura - Oliveira, Luiz da Conceição (2013)
This thesis aims at presenting a study about writer Rachel de Queiroz. We use her books O Quinze, Dôra, Doralina e Memorial de Maria Moura as the corpus for our research. This study is divided into three steps: first, we deal with the writer’s education, from early childhood, when she learned her first words and was in contact with the writers of 1930’s. Second, we talk about gender based on the protagonists: Conceição, Dôra, Doralina e Maria Moura. We show these stages through orphanhood, search, space, agreements and disagreements, as recurrent categories in Queiroz’s works. We discuss how these stages contributed to the characters’ independence, accomplishments and freedom.